Electron-phonon interaction effects in semiconductor quantum dots: a non-perturbative approach - Vasilevskiy, Mikhail (2004)
Multiphonon processes in a model quantum dot (QD) containing two electronic states and several optical phonon modes are considered by taking into account both intra- and nterlevel terms. The Hamiltonian is exactly diagonalized, including a finite number of multiphonon processes large enough to guarantee that the result can be considered exact in the physically important energy region. The physical properties are studied by calculating the electronic Green’s function and the QD dielectric function. When both the intra- and interlevel interactions are included, the calculated spectra allow several previously published experimental results obtained for spherical and self-assembled QD’s, such as enhanced two-LO-phonon replica in absorption spectra and up-converted photoluminescence to be explained. An explicit calculation of the spectral line shape due to intralevel interaction with a continuum of acoustic phonons is presented, where the multiphonon processes also are shown to be important. It is pointed out that such an interaction, under certain conditions, can lead to relaxation in the otherwise stationary polaron system.